Abdülmecid B. Nasuh Tosyevî Ve Matlab-I A’lâ Adlı Esma-İ Hüsna Şerhi - Sakar, Ekrem (My University, 2016)
Abdülmecid B. Nasuh Tosyevî ve Matlab-ı A’lâ Adlı Esma-i Hüsna Şerhi Bu çalışmanın konusu, XVI. yüzyılda yaşamış olan Abdülmecid B. Nasuh Tosyevî’nin telif ettiği ve Matlab-ı A’lâ adını verdiği esmâ-i hüsnâ şerhidir. h. 972 (m. 1564) yılında kaleme alınan eser Türkçedir. Esas itibariyle mensur olan eserde yer yer manzum kısımlar da bulunmaktadır. Karşılaştırmalı metin oluşturulurken eserin Süleymaniye Kütüphanesi’nde tespit edilen üç nüshası incelenerek bilimsel bir neşir hazırlanması amaçlanmıştır. Çalışmanın giriş kısmında esmâ-i hüsnâ kavramına dair verilmiş, sûfîlerin esmâ-i hüsnâya bakış açılarına değinilmiş ve esmâ-i hüsnâ şerhlerinin İslâmî Türk edebiyatındaki öneminden kısaca bahsedilmiştir. Birinci bölümde, kaynaklarda kendisi hakkında çok az bilgi verilen Abdülmecid B. Nasuh Tosyevî’nin hayatı, ilmî şahsiyeti ve eserleri hususunda tanıtıcı bilgiler verilmiştir. İkinci bölümde, araştırmaya konu olan Matlab-ı A’lâ muhteva ve şekil yönüyle incelenmiştir. Üçüncü bölüm, eserin metnine tahsis edilmiş, tenkitli neşir metoduyla hareket edilerek eserin orijinal haline en yakın metnin ortaya konması amaçlanmıştır. Esmâ-i Hüsnâ, Şerh, Abdülmecid B. Nasuh Tosyevî, Matlab-ı A’lâ, Metin İnceleme

Abdulmecid B. Nasuh Tosyevi and His Commentary of The Most Comely Names of Allah called Matlab-ı A’la This work regarding Matlab-ı A’la, which is a commentary of the Most Comely Names of Allah, was written by Abdülmecid B. Nasuh Tosyevî who lived in XVI. century. The work was written in h. 972/ a.d. 1564 in Ottoman Turkish. The work is mostly prosacial but it is also in verse. The research was strived to be written as scholary editing based on three copies which are found in Süleymaniye Library. The introduction deals with the concept of The Most Comely Names of Allah, The Most Comely Names of Allah according to sufis, and the Commentary of The Most Comely Names of Allah’s literary genre in Islamic Turkish literature. The first part of the research is a simple chronology of the life of Abdulmecid B. Nasuh Tosyevi because the information about the author of the book is fairly limited. This part of the research also includes the author’s scholarly life and works. The second part of the research ùouches on Matlab-ı A’la in point of its content and style. The third part of the research is regarding the matter of the text of the work. Critical editing method was used in order to render a work as close as possible to the original version of the work. Key words: The Most Comely Names of Allah, Commentary, Abdulmecid B. Nasuh Tosyevi, Matlab-ı A’la, Textual Criticism
Keywords: Abdülmecîd B. Nasûh Tosyevî, ?- 1588; İslam edebiyatı; Tarih